Meningkatkan Hasil Belajar Siswa Konsep Laju Reaksi dengan Model Discovery PjBL Berbasis STEM di SMAN 1 Lemahabang Cirebon - Ade Sri Rahayu; Joko Sutarno (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2021)
This research is a classroom action research which aims to improve the chemistry learning outcomes of the reaction rate concept by using the Discovery Project Based Learning (PjBL) model based on Science, Technology, Engineering, and Mathematics (STEM) at SMAN 1 Lemahabang, Cirebon Regency. This research was conducted in two cycles, each cycle consisted of 1-2 meetings. The subjects of this study were 34 students of class XI-MIPA 3 at SMAN 1 Lemahabang. The data collection instruments used in this research were a test method for students, monitoring the conditions of the teaching and learning process and questionnaires to find out students' responses to the learning carried out. Based on the research analysis showed that in the first cycle there was an increase in student learning outcomes in the concept of reaction rate, namely the value before being given action with good and very good criteria of 11,76% and after being given action the value was 44,11%, then in the second cycle it increased to 79, 41%, while students who scored below the Minimum Completeness Criteria experienced a decline. Therefore, the use of the STEM-based Discovery PjBL model could improve the chemistry learning outcomes of students on the reaction rate material.